Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

You throw a ball straight up from a rooftop. The ball misses the rooftop on its way down and eventually strikes the ground. A mathematical model can be used to describe the relationship for the ball's height above the ground, [tex]\( y \)[/tex], after [tex]\( x \)[/tex] seconds.

[tex]\[
\begin{array}{|c|c|}
\hline
x \text{ (seconds after the ball is thrown)} & y \text{ (ball's height in feet above the ground)} \\
\hline
1 & 359 \\
\hline
3 & 281 \\
\hline
4 & 194 \\
\hline
\end{array}
\][/tex]

a. Find the quadratic function [tex]\( y = ax^2 + bx + c \)[/tex] whose graph passes through the given points.

[tex]\( y = \boxed{\quad} \)[/tex]


Sagot :

To find the quadratic function [tex]\( y = ax^2 + bx + c \)[/tex] whose graph passes through the given points [tex]\((1, 359)\)[/tex], [tex]\((3, 281)\)[/tex], and [tex]\((4, 194)\)[/tex], we need to determine the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]. Let's consider each given point and substitute them into the quadratic equation:

For the point [tex]\((1, 359)\)[/tex]:
[tex]\[ 359 = a(1^2) + b(1) + c \][/tex]
Which simplifies to:
[tex]\[ a + b + c = 359 \quad \text{(Equation 1)} \][/tex]

For the point [tex]\((3, 281)\)[/tex]:
[tex]\[ 281 = a(3^2) + b(3) + c \][/tex]
Which simplifies to:
[tex]\[ 9a + 3b + c = 281 \quad \text{(Equation 2)} \][/tex]

For the point [tex]\((4, 194)\)[/tex]:
[tex]\[ 194 = a(4^2) + b(4) + c \][/tex]
Which simplifies to:
[tex]\[ 16a + 4b + c = 194 \quad \text{(Equation 3)} \][/tex]

Now, we can solve this system of equations:

[tex]\[ \begin{cases} a + b + c = 359 \\ 9a + 3b + c = 281 \\ 16a + 4b + c = 194 \\ \end{cases} \][/tex]

Step 1: Subtract Equation 1 from Equation 2 to eliminate [tex]\( c \)[/tex]:
[tex]\[ (9a + 3b + c) - (a + b + c) = 281 - 359 \\ 8a + 2b = -78 \\ 4a + b = -39 \quad \text{(Equation 4)} \][/tex]

Step 2: Subtract Equation 2 from Equation 3 to eliminate [tex]\( c \)[/tex]:
[tex]\[ (16a + 4b + c) - (9a + 3b + c) = 194 - 281 \\ 7a + b = -87 \quad \text{(Equation 5)} \][/tex]

Step 3: Subtract Equation 4 from Equation 5 to eliminate [tex]\( b \)[/tex]:
[tex]\[ (7a + b) - (4a + b) = -87 - (-39) \\ 3a = -48 \\ a = -16 \][/tex]

Step 4: Substitute [tex]\( a = -16 \)[/tex] back into Equation 4 to find [tex]\( b \)[/tex]:
[tex]\[ 4(-16) + b = -39 \\ -64 + b = -39 \\ b = 25 \][/tex]

Step 5: Substitute [tex]\( a = -16 \)[/tex] and [tex]\( b = 25 \)[/tex] back into Equation 1 to find [tex]\( c \)[/tex]:
[tex]\[ -16 + 25 + c = 359 \\ 9 + c = 359 \\ c = 350 \][/tex]

Thus, the quadratic function is:
[tex]\[ y = -16x^2 + 25x + 350 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.